Understanding the sleep of ultra-marathon swimmers: Guidance for coaches and swimmers - Dunican, I. C.; Perry, E. L.; Gemma, M.; Nesci, E.; Roberts, S. (International Journal of Sports Science & Coaching, 2023)
Open water swimming ultra-marathon events >10 km have become increasingly popular amongst master athletes. However, very little is known about the timing of training sessions and the impact on sleep. This study aimed to examine sleep behaviours, sleep problems and disorders and the relationship with training timings. This study used a longitudinal observational design for 42 nights with 24 masters' swimmers (n = 13 females), aged 39 ± 11 years, body mass index of 26 ± 3 kg/m2 during a training squad for an ocean ultra-swim (19.7 km) in Western Australia. Objective measures of sleep were obtained from a wrist-activity monitor, the Readiband™ (Fatigue Science Inc., Canada). Swimmers completed a survey instrument related to sleep problems, disorders, chronotype, anthropometric and demographic information. Generalised linear mixed models were fitted to examine relationships between predictor variables and sleep responses. Body mass index was associated with a decline in Total Sleep Time (TST), each one-unit increase in BMI was associated with 5 min less TST (p = 0.04). Swimmers with a "high risk" of sleep apnea had 21 min more wake time (p = 0.04) and 5% lower Sleep Efficiency (p = 0.04). Sleep Offset on the morning of a morning training session was earlier by 48 min (p < 0.001) resulting in less TST by 39 min (p < 0.001). This study provides evidence that coaches need to consider sleep behaviours and problems before designing training schedules. Swimmers need to plan and allocate an adequate sleep opportunity and those who have a suspected sleep disorder or problem should seek the support of a sleep physician.